Enhancing Spillway Efficiency Discharge Coefficients: Insights from Historical Models and Case Studies of Ogee, Lateral, and Non-Linear Structures - Nyflis, Emmanuel (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.